من أسرار ومعاني حروف الجر في القرآن الكريم نماذج مختارة From Meanings And Secrets Of Preposition In Holy Quran. Selected Models - هاجر, بوعكاز; نسيمة, ضاضي سيسطة (جامعة الوادي university of eloued, 2023)
هدف هذا المقال إلى الوقوف على الأبعاد الدلالية والأسرار البلاغية لحروف الجر في الخطاب القرآني، من خلال تتبع معانيها في آيات مختلفة، واستعمالات متنوعة المقاصد والغايات، بدءا من الوظيفة النحوية، التي تتمثل في تعدية الفعل إلى مفعول به. من أهم النتائج المتوصل إليها في هذا البحث، أن حروف الجر من أصغر البنى اللسانية في الخطاب القرآني المتعددة المعاني والأغراض والأبعاد، وكان الوقوف عند معانيها وطريقة توظيفها نقطة مميزة في بيان نظم وبلاغة القرآن الكريم. EThis article aims to examine the semantic dimentions and the rhetorical secrets of prepositions in the Quranic discourse by tracing their meanings in different verses and uses various purposes starting from the grammatical function that is represented in transposing the verb into its object. One of the most important results reached in this research is that the prepositions are one of the smallest linguistic structures in the Quranic discourse with multiple meanings,purposes and dimensions and stopping at their meanings and the way they are used is a distinctive point in the statement of the systems and rhetoric of the holy Quran
مقال
Keywords: حروف الجر ; القرآن ; البلاغة ; النظم